(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
This article aims to report the experience of the Interdisciplinary League in Mental Health (LISAM) during the new coronavirus pandemic. This is a report of experiences lived by LISAM members. With the pandemic of the new coronavirus and the closing of teaching intuitions, as a way of preventing contamination, LISAM, from the State University of Vale do Acaraú (UVA), found barriers to continue with the activities that make up the university tripod: teaching, research, and extension. Given this scenario, the League planned and developed some activities to promote mental health. Thus, the creation of informative videos and lives on the Instagram page and the organization of an online event was conducted. It was necessary to reorganize teaching and research activities based on the health crisis scenario. Academic Leagues enable students to get closer to the community, producing exchanges of experiences and more learning. LISAM managed, even if remotely, to fulfill the extension role during the pandemic. It was possible to reinvent and continue teaching, research, and extension activities in the pandemic. The crossing was full of challenges and learning.